A co-evolutionary interaction design of digital TV applications based on verbal decision analysis of user experiences. (20th May 2009) - Mendes, Marilia; Carvalho, Ana Lisse; Furtado, Elizabeth; Pinheiro, Placido
Since mobile TV represents a new paradigm for interaction design, many different candidate solutions of interaction can be possible. Following this concept, a study was accomplished with the objective of finding a better interaction solution for an application of mobile digital TV. Three executable prototypes of an application of mobile TV were built. A multicriteria model of verbal decision analysis was applied to those three alternatives by aiming at investigating the favourite characteristics of each prototype based on user's experience and their intentions of use. This model resulted in a method that supports designers in the qualitative analysis of alternatives and collaborative conception of the best solution of interaction to innovative products.